Discretion in Bonus Plans - Ederhof, Merle (The Accounting Review, 2010)
ABSTRACT: This study examines discretionary bonus payments by firms to senior-level executives. Interpreting discretionary bonuses as the result of implicit incentive contracts, I analyze an analytical model that includes a contractible and a non-contractible performance measure. The model yields the primary hypothesis that discretionary bonuses occur when the outcome of the contractible measure is either low or high, but not when the contractible outcome falls in the medium range. Based on a sample collected from public sources, I find empirical support for the notion that discretionary bonuses are paid based on non-contractible performance measures that are related to future financial performance. Moreover, discretionary bonus payments occur significantly more often when the contractible performance measure falls in the tails of the distribution. In contrast, I do not find support for the predictions that discretionary bonus payments are related to the manipulability of the contractible performance measures or that discretionary bonus payments are related to the power of the executives in the companies.